Folding List of Graphs Obtained from a Given Graph - E. M. El-Kholy; H. Ahmed (International Journal of Mathematics and Mathematical Sciences)
In this paper, we examine the relation between graph folding of a given graph and foldings of new graphs obtained from this graph by some techniques like dual, gear, subdivision, web, crown, simplex, crossed prism, and clique-sum graphs. In each case, we obtained the necessary and sufficient conditions, if exist, for these new graphs to be folded.